Nonspecific bowel activity in imaging inflammation with Tc-99m labelled monoclonal anti-NCA-90 Fab’ fragment MN3 - Ivančević, V.; Wolter, A.; Munz, D. L. (Nuklearmedizin - NuclearMedicine, 2001)
Aim: Since the Tc-99m labelled monoclonal anti-NCA 90 granulocyte antibody Fab’ fragment MN3 (MN3 Fab’) might be of interest for imaging abdominal inflammation which could be hampered by nonspecific bowel activity, we prospectively investigated the appearance of bowel activity in MN3 Fab’ imaging. Methods: Eighty consecutive patients (age range 12-85 years) referred for suspected nonabdominal, mostly musculoskeletal infection, were included. Abdominal inflammation was excluded clinically and there were no signs of inflammatory bowel disease in the patients’ histories. One, 5, and 24 hours after intravenous injection of up to 1.1 GBq of MN3 Fab’ planar images of the abdomen were performed. Bowel activity was graded visually using a 5-point scale. Results: The one (N = 80), 5 (N = 79), and 24 (N = 52) hour images revealed 46 (10%), 162 (34%), and 173 (55%) accumulating bowel segments, respectively, in 37 (46%), 69 (87%), and 52 (100%) patients. The mean intensity score per accumulating segment was 1.1,1.8 and 2.7 (p = 0), respectively. Relative frequencies of appearance of the small intestine were 38%, 57%, and 21%, ileocaecal region 6%, 53%, and 48%, ascending colon 5%, 67%, and 89%, transverse colon 1%, 9%, and 69%, descending colon 8%,15 %, and 67%, and rectosigmoid 0%, 4%, and 38%, respectively. Follow-up investigations in 13 patients revealed diverging uptake patterns. Conclusion: Nonspecific bowel activity is often present in the early and almost always and more intense, in the delayed images. Early imaging at one hour after administration seems feasible, but a loss in sensitivity has to be considered. Thus, nonspecific bowel activity can be anticipated to be a pitfall in imaging abdominal inflammation with MN3 Fab’.
Keywords: Antigranulocyte antibody; Fab’ fragment; nonspecific bowel activity